2012
DOI: 10.1063/1.3670743
|View full text |Cite
|
Sign up to set email alerts
|

Development of high current Bi and Au beams for the synchrotron operation at the GSI accelerator facility

Abstract: In this work, the latest results of developing high current ion beams of Au and Bi at GSI facility are described. The difficulties in the production of required charge state in vacuum arc discharge ion sources using the pure materials in the cathodes are discussed. As a possible solution, admix of a small amount of more refractory metal to the cathode material is considered. As a significant result, a dramatic improvement in the production of high charge state Bi ions using the mixed Bi-Cu cathodes (with 8%-15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 3 publications
0
10
0
Order By: Relevance
“…The latter results could be theoretically reproduced by Schülke and Anders [12]. Recently, Adonin and Hollinger reported on much higher Bi charge states when using composite Bi-Cu cathodes compared with when using elemental Bi [13]. Neutral metal vapor plays a critical role as pointed out in several studies [6], [13], [14].…”
Section: Introductionmentioning
confidence: 58%
See 2 more Smart Citations
“…The latter results could be theoretically reproduced by Schülke and Anders [12]. Recently, Adonin and Hollinger reported on much higher Bi charge states when using composite Bi-Cu cathodes compared with when using elemental Bi [13]. Neutral metal vapor plays a critical role as pointed out in several studies [6], [13], [14].…”
Section: Introductionmentioning
confidence: 58%
“…At first glance, the electron temperature model can also not explain the strong increase in the mean charge state from 1.06 for pure Bi to 3.94 for a Bi-Cu alloy with 10% Cu as reported by Adonin and Hollinger [13]. Anders and Yushkov, however, pointed out that the mean charge state of Bi is strongly influenced by the evaporation of neutrals during the pulsed arc discharge [14].…”
Section: B Processes In Cathode Spotsmentioning
confidence: 84%
See 1 more Smart Citation
“…Using the mixed material it became possible to increase the discharge current of vacuum arc up to 900 A without cathode malfunction. The charge state distribution of Bi-ions in the plasma during the discharge pulse was notably increased and distribution maximum was shifted to 4 + : 20% of 3 + , 66% of 4 + and 14% of 5 + [6]. The Cu-fraction in the ion spectrum was less than 20% (mostly Cu 3+ ions).…”
Section: B Cathodes From Bi-cu Mixturementioning
confidence: 94%
“…The GSI ion source group has shown that cathodes containing a small alloyed fraction of a more refractory metal mixed with the dominant less refractory metal, such as Au or Bi, can yield significantly increased higher charge state fractions (of Au or Bi) in the extracted ion beam [33].…”
Section: Recent Developmentsmentioning
confidence: 99%